Religious practice social changes during the COVID-19 pandemic in the United Arab Emirates. - B. Myrzabekova (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2021)
This article discusses some theoretical aspects of nation-building in the case of the United Arab Emir-ates and the social changes produced by COVID-19. Countries across the world responded very differently in their prevention and control of coronavirus disease and state capacity is likely driving these differences. The ongoing coronavirus pandemic, the related public health measures taken to mitigate the spread of the disease, and the varied public responses to the virus have far-reaching social implications. This case study explores United Arab Emirates’ experience on controlling pandemic in terms of state capacity. The main goal and purpose of this study is to analyze how social changes caused by COVID-19 pandemic affected religious life and state-society relations in terms of state capacity in the United Arab Emirates. The results of this study showed that state capacity has played an important role in effectively mitigating the widespread impact of the pandemic, which has led to a paradigm shift in all spheres of hu-man life, in particular in religious life. Based on the results of empirical research, we see that the society in the UAE quickly adapted to new realities and perceived these restrictions as temporary and a sense of trust in the state increased, thus emphasizing the importance of having a capable state.